2015
DOI: 10.1037/cns0000067
|View full text |Cite
|
Sign up to set email alerts
|

Intentional binding or perceptual repulsion? Binding in a general population sample decreases with age and increases with psychosis-like experiences.

Abstract: The sense of agency is an essential part of human experience. One aspect of agency, intentional binding, is the subjective contraction of time between a willful, voluntary action and the sensory consequences of that action. Previous studies of intentional binding have mainly been conducted with undergraduate samples. The present study utilized a 200- to 600-ms interval estimation task, with active and passive movements, to assess intentional binding in a community sample (mean age = 44.6, range = 21–60) in who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…The perceived interval was not significantly different between Passive and Other conditions (p = 0.87). This pattern of results, where intervals after active movements are perceived as longer compared to passive movements, is a phenomenon termed perceptual repulsion and has been demonstrated previously to be related to the age of the participants (Graham, Martin-Iverson, & Waters, 2015; see discussion below). For Pass.…”
Section: 2supporting
confidence: 72%
See 3 more Smart Citations
“…The perceived interval was not significantly different between Passive and Other conditions (p = 0.87). This pattern of results, where intervals after active movements are perceived as longer compared to passive movements, is a phenomenon termed perceptual repulsion and has been demonstrated previously to be related to the age of the participants (Graham, Martin-Iverson, & Waters, 2015; see discussion below). For Pass.…”
Section: 2supporting
confidence: 72%
“…-perceived intervals after Active movements to be longer than after Passive movements. We have previously demonstrated in the same sample of healthy controls as the current study that, at the 200 ms interval, younger adults experience intentional binding but this relationship changes with age such that older adults experience intervals after Active movements to be longer than after Passive movements, so-called 'perceptual repulsion' (Graham et al, 2015). We were therefore interested if increasing age was also responsible for the perceptual repulsion observed in Pass.…”
Section: 4mentioning
confidence: 65%
See 2 more Smart Citations
“…As arousing states are associated with alterations in the dopaminergic pathways within different brain areas (Damsma, Pfaus, Wenkstern, Phillips, & Fibiger, 1992 ; Giuliano & Allard, 2001 ), a reduction in action binding during arousal reflects the changes in the dopaminergic system involved in action execution (Tanaka et al, 2019 ). Previous researchers have already highlighted dopamine as a determinant of intentional binding (Aarts et al, 2012 ; Graham, Martin-Iverson, & Waters, 2015 ; Moore et al, 2010 ). Several studies have found hints for an involvement of the dopaminergic system in intentional binding, such as ketamine as a model for psychosis (Moore et al, 2011 ), schizophrenia (Haggard, Martin, Taylor-Clarke, Jeannerod, & Franck, 2003 ; Hauser et al, 2011 ; Hur, Kwon, Lee, & Park, 2014 ; Voss et al, 2010 ), psychosis-like experiences, and age (Graham et al, 2015 ), as well as substance use (Render & Jansen, 2019 ).…”
Section: Discussionmentioning
confidence: 99%